Nanoparticle delivery of an AKT/PDK1 inhibitor improves the therapeutic effect in pancreatic cancer - Lucero-Acuña A (Dove Medical Press, 2014)
Armando Lucero-Acuña,1 Justin J Jeffery,2 Edward R Abril,3,4 Raymond B Nagle,3,4 Roberto Guzman,1 Mark D Pagel,2,3,5,6 Emmanuelle J Meuillet3,7,8 1Department of Chemical and Environmental Engineering, University of Arizona, 2Department of Biomedical Engineering, University of Arizona, 3University of Arizona Cancer Center, 4Department of Pathology, University of Arizona, 5Department of Chemistry and Biochemistry, University of Arizona, 6Department of Medical Imaging, University of Arizona, 7Department of Molecular and Cell Biology, University of Arizona, 8Department of Nutritional Sciences, University of Arizona, Tucson, AZ, USA Abstract: The K-ras mutation in pancreatic cancer can inhibit drug delivery and increase drug resistance. This is exemplified by the therapeutic effect of PH-427, a small molecule inhibitor of AKT/PDK1, which has shown a good therapeutic effect against a BxPC3 pancreatic cancer model that has K-ras, but has a poor therapeutic effect against a MiaPaCa-2 pancreatic cancer model with mutant K-ras. To increase the therapeutic effect of PH-427 against the MiaPaCa-2 pancreatic cancer model with mutant K-ras, we encapsulated PH-427 into poly(lactic-co-glycolic acid) nanoparticles (PNP) to form drug-loaded PH-427-PNP. PH-427 showed a biphasic release from PH-427-PNP over 30 days during studies in sodium phosphate buffer, and in vitro studies revealed that the PNP was rapidly internalized into MiaPaCa-2 tumor cells, suggesting that PNP can improve PH-427 delivery into cells harboring mutant K-ras. In vivo studies of an orthotopic MiaPaCa-2 pancreatic cancer model showed reduced tumor load with PH-427-PNP as compared with treatment using PH-427 alone or with no treatment. Ex vivo studies confirmed the in vivo results, suggesting that PNP can improve drug delivery to pancreatic cancer harboring mutant K-ras. Keywords: nanoparticles, pancreatic cancer, AKT, bioluminescence imaging, drug delivery